Cooperative nucleation modes in polycrystalline CoxPd1-x nanowires - Viqueira, María Soledad (2015)
Polycrystalline CoxPd1-x (x=1, 0.60, 0.45, 0.23, and 0.11) cylindrical nanowires (ø=18-35nm, about 1μm length) are produced by AC electrodeposition into hexagonally ordered alumina pores. Single-phase nanowires of an fcc Co-Pd solid solution, with randomly oriented equiaxed grains (7-12nm) are obtained; in all the cases, the grain size is smaller than the wire diameter. The coercive field and the reduced remanence of Co-rich nanowire arrays are hardly sensitive to temperature within the range varying from 4K to 300K. On the other hand, in Pd-rich nanowires both magnitudes are smaller and they largely increase when cooling below 100K. This behavior also depends on the mean grain size. These facts are systematized considering two main aspects: the non-trivial temperature and composition dependence of the crystalline anisotropy and the saturation magnetostriction in Co-Pd alloys; and a random anisotropy effect, which defines a nucleation localization length that may involve more than a single grain, and thus promotes more cooperative nucleation modes.